2013
DOI: 10.1021/jp312191c
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and High-Temperature Persistent Photoconductivity Experiments in SnO2 Nanobelts

Abstract: The Persistent Photoconductivity (PPC) effect was studied in individual tin oxide (SnO 2 ) nanobelts as a function of temperature, in air, helium, and vacuum atmospheres, and low temperature Photoluminescence measurements were carried out to study the optical transitions and to determine of the acceptor/donors levels and their best representation inside the band gap. Under ultraviolet (UV) illumination and at temperatures in the range of 200 to 400K we observed a fast and strong enhancement of the photoconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(94 citation statements)
references
References 33 publications
6
86
2
Order By: Relevance
“…The phenomenon of persistent photoconductivity (PPC) [21] has been found in rare-earth doped SnO 2 [22]. More recently, PPC has been found in SnO 2 nanobelts [23] and quantum dots [24]. Modeling the decay of PPC,…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The phenomenon of persistent photoconductivity (PPC) [21] has been found in rare-earth doped SnO 2 [22]. More recently, PPC has been found in SnO 2 nanobelts [23] and quantum dots [24]. Modeling the decay of PPC,…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…[14][15][16]22,[31][32][33][34][35][36][37][38][39][40] However, the peak position of the reported PL bands depends on the growth method and/or growth parameters used. [14][15][16]22,[31][32][33][34][35][36][37][38][39][40] However, the peak position of the reported PL bands depends on the growth method and/or growth parameters used.…”
Section: Resultsmentioning
confidence: 99%
“…The peak at ܲ ଵ ௌ violet emission might be due to near band edge emission 31 . Viana et.al 13 assigned the similar peak of ܲ ଵ ௌ to recombination of electrons from the CB to excitons bound to neutral (D 0 x). Kim et.al., 67 observed the peak at 416 nm (2.98 eV), but in the present studies a broad peak at ܲ ଶ ௌ is identified.…”
Section: Photoluminescencementioning
confidence: 93%
“…Since the energy of the emission band is lower than the band gap energy of SnO 2 (E g = 3.6 eV) 13,68 , the emission is not due to the direct recombination of a conduction electron in the 4p band of Sn and a hole in 2p VB of O 69 . The peak at ܲ ସ ௌ is assigned to isolated V O + centers, which lies at higher energy than the complex V O + center Ref 13 . In R 2 (see Fig 6d), a broad orange emission peaks identified as ܲ ହ ௌ and ܲ ௌ positioned at 562 and 585 nm.…”
Section: Photoluminescencementioning
confidence: 97%